Multi-functional music player on the iPhone - Phey, Fabian Kee Yeong. (2010)
Macintosh based platforms have surged in popularity in recent years. As such, more and more developers are developing applications for these platforms. The release of one such platform (the iPhone) has revolutionised the entire smart phone industry. The iPhone’s massive popularity coupled with the release of the iPhone Software Development Kit and subsequently the launch of the Apple Appstore, have resulted in a frenzy of developers creating applications for this incredibly popular platform. This report will explore the entire process, relevant knowledge and tools necessary to develop for the iPhone platform.